Search for knowledge and professional scepticism of accounting students – an experimental study - Ciołek, Maciej (Research Papers of Wrocław University of Economics, 2018)
The purpose of this study is to examine whether university accounting programs shape such ‘search for knowledge’ trait in significantly more effective comparing other university programs in the field of economy. For this purpose I conducted an experimental study using Hurtt Professional Skepticism Scale – HPSS which is one of the most recognized skepticism measures. I surveyed 432 students of Poznań University of Economics who follow either accounting program or management program (control group). The results showed that only programs in accounting increased the mean level of ‘search for knowledge’ trait significantly comparing to management program. The robustness analysis showed that gender, professional experience and length of service had no statistically significant impact on results
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2018; Nr 515; s. 243-257
Keywords: auditing; search for knowledge; accounting students; experimental study; HPSS; audyt; szukanie wiedzy; studenci rachunkowości; badanie eksperymentalne